Pattern of Oral Cancer in India: An analysis of Hospital Based Cancer Registry data - Anu Babu; Rohan T Mathew; Rohan Shetty (Wolters Kluwer Medknow Publications, 2023)
Background: Oral cancer is a major public health burden in India, accounting for one-fourth of the global burden and being the most common cancer among males. Objectives: We intend to analyze oral cavity cancer data retrieved from the Report of Hospital-Based Cancer Registry (HBCR) 2021. Materials and Methods: The study primarily collected oral cancer data from the HBCR report published in 2021. This study aimed to identify the pattern of incidence and distribution of oral cancer, clinical stages at the time of diagnosis, and the overall treatment delay in hospitals across the country. Results: The study found that among cancers associated with tobacco, oral cancers are the most common, accounting for 42.1% of cases in males and 42.7% in females. The locoregional stage is the most common stage at diagnosis for both mouth and tongue cancers in both genders. Treatment for oral cancers is generally delayed, with only 9.2% of cases starting treatment within 7 days. Conclusion: India has a high and rising incidence of oral cancer, necessitating comprehensive guidelines for screening, treatment, and palliative care to lower its incidence and mortality.